The personal electronic monitoring as a measure to reduce overcrowding in prisons - Neyra Villanueva, Javier Alejandrino (2022)
The main objective of this paper is to show how electronic surveillance will serve as a preventive coercive measure in judicial processes, since it will prevent overcrowding in prisons. This results in overcrowding and the lack of separation between the accused and the convicted, and has repercussions on the guarantor position that States have towards persons deprived of their liberty, in relation to the principle of humane treatment, the right to life and personal integrity of those persons who, while still being prosecuted, are deprived of their liberty, since this measure should be the exception and not the rule. In this sense, we will review the concepts of electronic surveillance, the importance of its application, as well as other studies prior to it, in order to raise awareness to avoid existing prison problems.